Kalapodi, Griechenland. Neue Forschungen in der Umgebung der Tempelkomplexe - Sporn, Katja (e-Forschungsberichte des DAI, 2017)
The sanctuary of Kalapodi in Phocis (central Greece) has been excavated since the 1970s by R. C. Felsch. In the early campaigns, the fieldwork focused on the foundation of the Northern Temple and its predecessors, before the Southern Temple was found and systematically examined between 2004 and 2013 by W.-D. Niemeier. The recent campaigns of 2014 to 2016 led by K. Sporn aimed at a general study of the sanctuary’s area and infrastructure to find answers to the following questions: Can we surely identify the sanctuary of Kalapodi as the oracle of Abai – and where is the town of Abai to be located then? Is it an urban, suburban or even an extra urban sanctuary? Is it possible to determine the sanctuary’s boundaries and how are sacred and profane spaces distributed throughout its area?